Managers#x2019; Intention on Diversification Strategies for firm Performance in the Health Care Industry of Sri Lanka (Global Journal of Management and Business Research, 2019)
This study focused because of the diversification is an interesting area of the company#x2019;s growth strategies. Today every companies or industry are driving for diversification strategies to grow their businesses. Many companies#x2019; success in diversification and some companies are failed. The implementing of diversification strategies are involves with managerial skills like managers knowledge, experience, and their productivity. Today markets expected to face more challenges and increasing high competition in the healthcare industry in Sri Lanka. Also the markets have become more competitive, to keep the cost structure in the low level is crucial for the firms in the long-run for their survival. The formal opinion is that diversification strategies are linked with both costs factors and the bene fits to the firm. Today implementing diversi fication strategies in many industries are highly imputable to the power to cross-sell their products, get cost savings, enter the new markets, produce hybrid products and increase brand image. This study is mainly focused on the managerial skills of the managers#x2019; who intention in diversification strategies. The study used a questioner and was distributed among 31 pharmaceutical managers in the Sri Lankan healthcare industry. Results were analyzed using SPSS. Finally research has provided directions for diversification strategies with different managerial skills to drive with firm performance.
Keywords: diversification strategies; firm performance; managerial skills